Periprocedural myocardial infarction after carotid endarterectomy and stenting: Systematic review and meta-analysis - Marion Boulanger (2018)
© 2015 American Heart Association, Inc. Background and Purpose-Carotid angioplasty and stenting (CAS) is associated with higher risk of periprocedural stroke and death when compared with carotid endarterectomy (CEA). By contrast, the risk of myocardial infarction (MI) was higher after CEA than after CAS in randomized trials. However, numbers were small, and risk factors are unknown. Methods-We performed a systematic review and a meta-analysis of studies published from January 1980 to June 2014 and collected unpublished data. We extracted data on 9 predefined risk factors (age, contralateral carotid occlusion, coronary artery disease, diabetes mellitus, sex, hypertension, peripheral artery disease, type stenosis, and clinical presentation). We selected studies with data available on MI in at least 1 subgroup, calculated absolute and relative risks, and identified differential effects on risks of MI. Results-The 30-day absolute risk of MI was 0.87% (95% confidence interval, 0.69-1.07) after CEA and 0.70% (95% confidence interval, 0.54-0.88) after CAS (Pint=0.38). After CAS, patients with symptomatic stenosis and restenosis were at higher risk of MI, whereas men were at lower risk. After CEA, age, history of coronary artery disease, peripheral artery disease, and restenosis increased the risk of MI. Only the effect of sex differed between CAS and CEA with men being at lower risk of MI than women after CAS, whereas there was no difference between after CEA (Pint=0.01). Conclusions-The risk of MI after CEA and CAS did not significantly differ. Risk factors for MI are overall similar in both techniques except that men are at lower risk of MI after CAS but not after CEA.